PENGEMBANGAN KAWASAN STRATEGIS PARIWISATA DI KABUPATEN GOWA: ANALISIS PEMANGKU KEPENTINGAN - Taba, Muhammad Idrus; Maupa, Haris; Parawansa, Dian Anggraece Sigit; Ismail, Muhammad; Pahlevi, Cepi (ITB AAS Indonesia Surakarta, 2024)
This research aims to identify and classify and describe the relationship between stakeholders involved in the development of KSPK Tinggimoncong and its surroundings. This study uses a descriptive type of research with qualitative methods. Data and information collection techniques are carried out by direct observation in the field, in-depth interviews, and literature studies. Based on the results of the study, there are 14 stakeholders consisting of the government, both categories of institutions at the National, Provincial, District, Sub-District, village, community, and private sectors through Destination Management, Corporate Social and Environmental Responsibility funds, to other rights such as tourism entrepreneurs, educational institutions, and the media. Stakeholder analysis resulted in four classifications of regional stakeholders, including (a) key players, namely the Gowa Tourism and Culture Office, the Gowa regency Regional Planning Agency, (b) subject, consisting of Pokdarwis Malino and companies, namely Perum Perhutani, PLN, PTPN XIV (c) context setter, including the Ministry of Tourism at the central government level, BKSDA South Sulawesi and BPCB South Sulawesi at the provincial government level, and the Gowa, Gowa environmental service, BPBD Gowa, Department of industry and trade Gowa, Dinsospmd Gowa,, tourism entrepreneurs, media, educational institutions, NGOs, health facility providers.